2020
DOI: 10.1590/0074-02760200115
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Angiostrongylus cantonensis in both humans and the snail Achatina (Lissachatina) fulica in the city of Macapá, in the Amazon Region of Brazil

Abstract: In January and February 2019, a malacological survey was conducted in the area surrounding the residence of a 12-year-old child that had contracted cerebral angiostrongyliasis in the municipality of Macapá, capital of the Amapá State, northern Brazil. The serological examination was positive for Angiostrongylus cantonensis infection, the principal etiological agent of this parasitosis. A sample of 54 molluscs was artificially and individually digested for parasitological analysis, containing 38 specimens of Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The presence of terrestrial molluscs living close to rodents and related to A. cantonensis infection, as B. willibaldoi and R. norvegicus in São Paulo city, highlights the need for surveillance mechanisms in order to avoid nematode spread throughout São Paulo territory. The finding of A. cantonensis definitive hosts and naturally infected intermediates in urban areas of Brazil reinforces the need to form specialized technical groups focused on scientific studies of the aspects that affect population dynamics of rodents and molluscs against the risk of transmission in the country ( Morassutti et al., 2014 ; Ramos de Souza et al., 2018 ; Orico et al., 2019 ; Barbosa et al., 2020 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The presence of terrestrial molluscs living close to rodents and related to A. cantonensis infection, as B. willibaldoi and R. norvegicus in São Paulo city, highlights the need for surveillance mechanisms in order to avoid nematode spread throughout São Paulo territory. The finding of A. cantonensis definitive hosts and naturally infected intermediates in urban areas of Brazil reinforces the need to form specialized technical groups focused on scientific studies of the aspects that affect population dynamics of rodents and molluscs against the risk of transmission in the country ( Morassutti et al., 2014 ; Ramos de Souza et al., 2018 ; Orico et al., 2019 ; Barbosa et al., 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…The ability of A. cantonensis to infect native or introduced species of terrestrial molluscs was demonstrated by a research conducted in the islands of Hawaii that showed the importance of molluscs as intermediate hosts for this parasite with high rates of infection ( Kim et al., 2014 ). In Brazil, eight species of terrestrial molluscs and one from freshwater were found naturally infected by A. cantonensis in 11 states ( Morassutti et al., 2014 ; Ramos de Souza et al., 2018 ; Orico et al., 2019 ; Barbosa et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiostrongylus cantonensis ( A. cantonensis ), is a food-borne zoonotic parasite that can cause damage to the central nervous system (CNS) ( Wang et al., 2012 ). With the development of global logistics transportation and climate warming, A. cantonensis has spread from its traditional endemic regions of Southeast Asia and the Pacific islands to the American continent, Europe, Africa and Australia ( Gelis et al., 2011 ; Iwanowicz et al., 2015 ; Liu et al., 2018 ; Rael et al., 2018 ; Barbosa et al., 2020 ; Federspiel et al., 2020 ). Angiostrongyliasis has become a potentially fatal globally emerging infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…So far, nearly 3000 cases of human angiostrongyliasis have been documented worldwide [3]. With the development of global logistics transportation and climate warming, A. cantonensis has spread from its traditional endemic regions of Southeast Asia and the Paci c islands to the American continent, Europe, Africa and Australia [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%